Collective Impact on Prevention: Let's Talk About Children Service Model and Decrease in Referrals to Child Protection Services - Niemelä, Mika; Kallunki, Hannu; Jokinen, Jaana; Räsänen, Sami; Ala-Aho, Birkitta; Hakko, Helinä; Ristikari, Tiina; Solantaus, Tytti (Frontiers in Psychiatry, 2019)
Background: Families with parental mental health issues often have numerous problems needing multilevel measures to address them. The “Let's Talk about Children Service Model (LT-SM)” is a community-based service approach aiming at collectively impacting population needs regarding child protection services. Three municipalities in the Raahe District (RD) of Finland requested implementation of the LT Service Model. This paper describes the model and first results. Methods: The LT Service Model connects relevant stakeholders with families and their social networks aiming at the shared goal of supporting children's everyday life at home, kindergarten, school, and leisure environments. Parents, teachers, and other caretakers are supported by LT interventions. An infrastructure for collaboration, decision making, monitoring, training, and feedback is established, embracing health, social and educational services, and other stakeholders. Referrals to child protection services were compared with national data before (2009–2013) and after implementation of the LT Service Model (2013–2016). Analyses were conducted using the joinpoint regression method. Results: There was a significant decrease in the underage population referred to child protection services in RD (AAPC = −6.9; p = 0.013) between 2013 and 2016, in contrast with an increased rate nationwide (AAPC = 1.9; p = 0.020). Conclusion: In the LT Service Model, prevention starts in children's everyday life as the uniting, common goal for multiple stakeholders and an integrated service structure is developed to support this effort. The first results are promising, showing an appreciable decrease in referrals to child protection services, although further research with longer follow-up and across other municipalities is needed.